The Factors of Failure to Exclusively Breastfeed In the BLUD UPTD Working Area of the Kandai Public Health Center of Kendari City: Exclusively Breastfeed - Dina, Hasniah; Krismiadi, Dedi; Apriyanti, Apriyanti (STIKes Mandala Waluya Kendari, 2024)
Background: Mother's milk (ASI) is a baby's need which is very necessary for the baby's growth and development. However, if exclusive breastfeeding is not provided, it can cause problems with the baby's growth and development Methods: This type of research is quantitative research using a cross-sectional study design, where the type of research emphasizes measuring/observing the independent and dependent variables only once at a time. This research involved 90 respondents. Results: In this study, the results showed that there was no relationship between working mothers and failure to provide exclusive breastfeeding in the Kandai Community Health Center working area with a Fisher's Exact Test value = 0.450 > 0.05. There is a relationship between social support and failure to provide exclusive breastfeeding in the Kandai Health Center working area with a calculated X2 value > X2 table. and there is a relationship between the promotion of formula milk and failure to provide exclusive breastfeeding in the Kandai public Health Center working area, the value of X2 calculated > X2 table. Conclusions: Promotion of formula milk, social support and no relationship between working mothers and the failure of exclusive breastfeeding in the Kandai Health Center working area. So it is necessary to pay attention to mothers who have babies <6 months to be able to provide exclusive milk to maintain the baby's growth and development well.